Pengaruh Penambahan Trass Dan Abu Kayu Bakar Terhadap Pengujian CBR Dan Permeabilitas Tanah Lempung - Alfarizi, Andi Azhari; Setiawan, Arman; Yuniarto, Eka (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
Development in Indonesia continues to develop along with advances in technology, many types of soil have been discovered to improve the quality of clay soil, which is often done through various stabilization techniques. One method that has attracted attention is the addition of Trass and Firewood Ash. Trass, which is a volcanic-based additive, has pozzolanic properties which can improve its carrying capacity, firewood ash as a by-product of wood burning waste. The aim of this research is to find out how much influence the addition of trass and firewood ash has on clay soil. In this research, CBR and Permeability testing was carried out with substitution of 10% trass at variations of 10%, 15% and 20%. And add firewood ash as much as 5%, 10%, 15% and 20%. The CBR and Permeability values have increased successively. The CBR value of the original soil was 13.03%, the soil with a mixture of 5% firewood ash and 10% firewood ash had CBR values of 21.85 and 22.16, while the CBR value with a mixture of trass and firewood ash was 32.96%, 42.67 % and 53.32%. Meanwhile, the permeability value for the original soil is 0.0039%, for soil with variations of 5% firewood ash and 10% firewood ash the permeability value is 0.0048cm/m3 and 0.0057cm/m3, while the permeability value with a mixture of trass and firewood ash is 0 .0066cm/m3, 0.0078cm/m3 and 0.0086cm/m3